Place Branding: Connecting Tourist Experiences to Territories - Corbisiero, Fabio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Tourism involves different organizations with different aims, such as public or private sectors nongovernmental or associations and even communities. Even in the context of marketing concerns, more specifically in the promotion and branding of a location, the scenario of various stakeholders is evident (e.g. a city, a region or a country). Countries, cities, and areas that serve as tourist destinations compete with one another to draw visitors, residents, and business investment.